Foreign debt, capital controls, and secondary markets: Theory and evidence from Nazi Germany - Andrea Papadia; Claudio A. Schioppa (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
We investigate how internal distribution motives can interfere with the economic objectives of capital controls. In order to do this, we provide a model showing that elite capture can affect optimal debt repatriations and the management of official reserves under capital controls. Relying on these theoretical insights and a wealth of quantitative and qualitative historical evidence, we study one of history's largest debt repatriations - that of 1930s Germany. We show that the authorities kept private repatriations under strict control, thus avoiding detrimental macroeconomic effects, while allowing discretionary repatriations in order to reap internal political benefits.
Keywords: E65; F38; H63; N24; 330; Sovereign risk; Capital controls; Elite capture; Germany; Nazi regime; Foreign debt; Secondary markets